2021
DOI: 10.3390/v13101989
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutations in the Glycoprotein Ectodomain of Field Rabies Viruses Mediate Cell Culture Adaptation through Improved Virus Release in a Host Cell Dependent and Independent Manner

Abstract: Molecular details of field rabies virus (RABV) adaptation to cell culture replication are insufficiently understood. A better understanding of adaptation may not only reveal requirements for efficient RABV replication in cell lines, but may also provide novel insights into RABV biology and adaptation-related loss of virulence and pathogenicity. Using two recombinant field rabies virus clones (rRABV Dog and rRABV Fox), we performed virus passages in three different cell lines to identify cell culture adaptive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
6
0
2
Order By: Relevance
“…Being located on the surface of RABV particles, the G-protein controls receptor binding and the release of the viral ribonucleoprotein (RNP) in the cytoplasm via pH-dependent membrane fusion, thereby playing a crucial role in the cell entry and in vivo spread [ 128 ]. Furthermore, it was shown that the G-protein (in particular, its ectodomain) accumulates adaptive mutations that improve the release of infectious viral particles [ 129 ].…”
Section: Resultsmentioning
confidence: 99%
“…Being located on the surface of RABV particles, the G-protein controls receptor binding and the release of the viral ribonucleoprotein (RNP) in the cytoplasm via pH-dependent membrane fusion, thereby playing a crucial role in the cell entry and in vivo spread [ 128 ]. Furthermore, it was shown that the G-protein (in particular, its ectodomain) accumulates adaptive mutations that improve the release of infectious viral particles [ 129 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, we employed RNA transcripts as standard for multiple reasons, among them the lower biosafety level required and the reliability of the target sequence compared to cell-adapted strains. Indeed, lyssaviruses amplification not only requires biosafety level 3 laboratory facilities, but more importantly induces the fixation of genetic mutations occurring during virus adaptation to a cell substrate, which might critically affect the evaluation of the assay performance [ 39 , 40 ]. Consistently with this, in the framework of previous research activities, in the cell-adapted LLEBV, we observed a G11A mutation within the 3′ non-coding region where LN34/(n)LN34 forward primers bind ( Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Being located on the surface of RABV particles, the G-protein controls the receptor binding and the release of the viral ribonucleoprotein (RNP) in the cytoplasm via the pH-dependent membrane fusion, thereby playing a crucial role in the cell entry and in vivo spread [124]. Furthermore, it was shown that the G-protein (in particular, it's ectodomain) accumulates the adaptive mutations improving the release of infectious viral particles [125].…”
Section: Functional Disorder In the G-proteinmentioning
confidence: 99%